Feminist Perspectives on Women's and Gender Roles in Indian Literature: Examining the Role of Feminist Literature in Challenging Gender Roles (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Female writers' works provide light on their role in literature's ideological past, while alsoreinforcing class-based cultural disputes. The current thesis examines some of the aforementioned vitalcomponents of feminist literature as well as about of the most well-known feminist authors. The primarygoal of this investigate is to shed light on key aspects of feminism, major historical periods of feminism,and prominent feminist authors. In other words, it's a worldview that draws on the idea of gender frommany different academic perspectives (Zalewski, 341). All feminist perspectives, despite theirdifferences, aim for a world in which men and women are treated as equals. Bell Hooks wrote a booktitled Feminism is for Everybody with the overarching goal of putting an end to all forms of sexism,including but not limited to discrimination based on gender. In this work, she argues that sexism is anissue and that it exacerbates societal issues. This research concludes by recognizing and appreciatingthe efforts of these modern Postcolonial women writers, who have been challenging and resisting thehegemonic power discourses in postcolonial societies, enabling women to speak and listen to eachother, and redefining their identities with the help of liberating tools like safe spaces that they havecreated through their gender-sensitive writings.